Merdeka Belajar Dalam Pandangan Alqur’an Hadis - Yustin Kamaru; Kasim Yahiji; Rahmin Thalib Husain; Ilyas Daud (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Merdeka belajar is a concept of education that gives learners the freedom to learn according to their interests, talents, and abilities. This concept is in line with the Islamic view that learning is a duty and a need for every human being. In the Qur'an, the concept of merdeka belajar can be found in several verses, such as QS Al-Alaq verse 1-5 which commands humans to read and learn. This verse shows that learning is important and must be done by every human being. In the hadith, the concept of merdeka belajar can also be found. For example, in a hadith narrated by Al-Bukhari, the Prophet Muhammad PBUH said, "Seeking knowledge is obligatory for every Muslim." This hadith shows that learning is obligatory for every Muslim, both men and women. Based on the view of the Qur'an and hadith, merdeka belajar can be interpreted as the freedom of learners to learn according to their interests, talents, and abilities. This freedom must be balanced with the responsibility of learners to study hard and achieve maximum results